Coordinated regulation of starch synthesis in maize endosperm by microRNAs and DNA methylation. (28th November 2020) - Hu, Yufeng; Li, Yangping; Weng, Jianfeng; Liu, Hanmei; Yu, Guowu; Liu, Yinghong; Xiao, Qianlin; Huang, Huanhuan; Wang, Yongbin; wei, Bin; Cao, Yao; Xie, Ying; et al.
SUMMARY: Starch synthesis is an essential feature of crop filling, but knowledge of the molecular mechanisms regulating the expression of starch synthesis genes (SSGs) is currently limited to transcription factors (TFs). Here, we obtained transcriptome, small RNAome, and DNA methylome data from maize ( Zea mays ) endosperms during multiple developmental stages and established a regulatory network atlas of starch synthesis. Transcriptome analysis showed a sharp transition at 9–10 days after pollination, when genes involved in starch and sucrose metabolism are upregulated and starch accumulates rapidly. Expression pattern analysis established a comprehensive network between SSGs and TFs. During maize endosperm development, the miRNAs with preferential repression of the expression of TFs, particularly the TFs regulating SSG expression, were extensively downregulated. Specifically, ZmMYB138 and ZmMYB115 affected the transcriptional activities of Du1 / Wx and Ae1 / Bt2 genes at their respective promoter regions. Remarkably, the two TFs were negatively regulated by the copious expression of Zma‐miR159k‐3p at the post‐transcriptional level. This suggests that miRNAs are important regulators of starch synthesis. Moreover, with the exclusion of the TFs, the expression of both SSGs and miRNAs was globally regulated by DNA methylation. Altogether, the present results (i) establish the regulatory functions of miRNAs and DNA methylation in starch synthesis and (ii) indicate that DNA methylation functions as a master switch. Significance Statement: Our knowledge of the molecular mechanisms regulating the expression of starch synthesis genes (SSGs) in crop cereals is currently limited to transcription factors (TFs). Here, we established a multi‐level transcriptional regulatory atlas of DNA methylation–miRNA–TF–SSGs in maize starch synthesis. In brief, the TFs regulate the expression of SSGs, while miRNAs modulate the expression of TFs, and the expression of SSGs and miRNAs, excluding TFs, is globally repressed by DNA methylation.